1989
DOI: 10.1093/ajcp/91.6.704
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Giardia Antigen in Stool with the Use of Enzyme Immunoassays

Abstract: Enzyme-linked immunosorbent assays (ELISAs) using sera from rabbits and goats immunized with Giardia trophozoites were compared for detection of Giardia antigen in 300 stool specimens, 80 of which had positive results for Giardia by microscopic examination. The diagnostic accuracy of the two assays was similar, with sensitivities of 92% and 87% and specificities of 87% and 91% with the use of rabbit and goat antisera, respectively. Both ELISAs detected Giardia antigen in stool samples from asymptomatic as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
0
6
1
Order By: Relevance
“…Some authors reported that the storage of stools as formalinized eluates did not affect the immunoenzymatic assay 21,25 . In contrast other studies 14,28 related poor results in such conditions. The current study evaluates the sensitivity and specificity of the ProSpecT Giardia Microplate Assay in fresh and formalinized stools of patients in Belo Horizonte, Brazil.…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Some authors reported that the storage of stools as formalinized eluates did not affect the immunoenzymatic assay 21,25 . In contrast other studies 14,28 related poor results in such conditions. The current study evaluates the sensitivity and specificity of the ProSpecT Giardia Microplate Assay in fresh and formalinized stools of patients in Belo Horizonte, Brazil.…”
Section: Introductioncontrasting
confidence: 58%
“…The fact that 10% Formalin is often used to preserve the specimens to be sent to the laboratories allows us to conclude that the test is useful for individual diagnosis as well as for epidemiological purposes. In contrast, UNGAR et al (1984) and KNISLEY et al (1989) reported that the presence of 10% Formalin affects the immunoassay. However, the antigen to be captured in these assays was not the GSA 65.…”
Section: Discussionmentioning
confidence: 94%
“…The ELISA test showed 76 samples positive for Giardia antigen and 120 negative (Table). developed previously. Enzyme immunoassays use either the direct (Green et al 1985, Knisley et al 1989, Torres et al 1997 or indirect methods. The test described herein is based on the direct method with the advantage of using polyclonal anti-Giardia antibodies as capture reagent, and the same antibodies linked to an enzyme as conjugate for detecting the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Previous immunoassays for detection of Giardia antigen in fecal sample eluates have included counterimmunoelectrophoresis (CIE) (Craft & Nelson 1982), enzyme-linked immunosorbent assay (ELISA) (Ungar et al 1984, Green et al 1985, Nash et al 1987, Knisley et al 1989, McLaughlin et al 1993, Torres et al 1997, Fedorko et al 2000 and dot-ELISA . The sensitivity of these methods has varied from 88 to 98% with CIE, and from 68 to 100% for the ELISA; their specificity has ranged from 90 to 97% for CIE, 81-100% for ELISA, and 100% for dot-ELISA.…”
mentioning
confidence: 99%
“…ELISAs have previously been developed for detection of E. histolytica and G. lamblia antigens in fecal specimens (10,11,13,19,20,24,26,(30)(31)(32). For E. histolytica, an ELISA using a single conjugated specific antibody was developed in 1978 (19), followed in 1982 by a double-antibody ELISA system (11), further modified in 1985 to a double-antibody ELISA using a monoclonal antibody (31).…”
Section: Discussionmentioning
confidence: 99%